2003
DOI: 10.2174/1568026033452348
|View full text |Cite
|
Sign up to set email alerts
|

Small-Molecule Inhibitors of Actin Dynamics and Cell Motility

Abstract: Cell motility is a central feature of a range of normal and pathological processes, including embryonic development, tissue repair, immune cell function, angiogenesis, and cancer metastasis. The dynamics of the actin cytoskeleton power cell migration. A large number of proteins are known or suspected to play roles in regulating actin dynamics. While there are now many available small molecules that target the actin cytoskeleton directly, there is a paucity of specific inhibitors of actin-binding proteins and o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
153
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 192 publications
(162 citation statements)
references
References 238 publications
5
153
1
Order By: Relevance
“…Recently, numerous studies have provided evidence that cytoskeletal mechanics play an essential role in the translocation of GLUT4 to the plasma membrane (22,23,39,(52)(53)(54)(55)(56)(57)(58). In particular, pharmacological disruption of cortical F-actin causes a profound disturbance in GLUT4 translocation and glucose transport (23,55,59). Although these data are consistent with the conclusion that the cellular cytoskeleton is involved in the translocation of GLUT4 to the plasma membrane, they have all been carried out in cultured cell model systems.…”
Section: Discussionsupporting
confidence: 60%
“…Recently, numerous studies have provided evidence that cytoskeletal mechanics play an essential role in the translocation of GLUT4 to the plasma membrane (22,23,39,(52)(53)(54)(55)(56)(57)(58). In particular, pharmacological disruption of cortical F-actin causes a profound disturbance in GLUT4 translocation and glucose transport (23,55,59). Although these data are consistent with the conclusion that the cellular cytoskeleton is involved in the translocation of GLUT4 to the plasma membrane, they have all been carried out in cultured cell model systems.…”
Section: Discussionsupporting
confidence: 60%
“…Small molecule marine natural products that target actin filaments with high affinity and potently interfere with actin filament dynamics have been shown to display cytotoxicity against several forms of multidrug resistant tumors (2)(3)(4)(5)(6)(7). For this reason, their candidacy as clinical chemotherapeutic treatments has gained significant attention (8).…”
mentioning
confidence: 99%
“…Therefore, small molecules whose modes of action on actin are different from cytochalasins were required. During the last 20 years a large number of highly cytotoxic compounds were isolated from marine organisms (König et al 2006;Nagle et al 2006), and quite a few of these have been shown to affect actin filaments (Spector et al 1999;Fenteany and Zhu 2003). Interestingly, the majority of them mimic endogenous actin-binding proteins (McGough et al 2003;Silacci et al 2004).…”
Section: Actinmentioning
confidence: 99%
“…Natural product inhibitors of actin cytoskeleton dynamics are not only recognized as valuable molecular probes for dissecting complex mechanisms of cellular function, but also their potential use as chemotherapeutics has become a focus of scientific investigation. Cytoskeletal inhibitors are lethal to tumor cells and several of them have been included in the National Cancer Institute's Molecular Targets Development Program (Fenteany and Zhu 2003;Spector et al 1999). So far, however, no actin-binding drugs have entered clinical trials due to their lack of selectivity for diseased cells.…”
Section: Actin-targeted Marine Toxins In Basic and Preclinical Studiesmentioning
confidence: 99%
See 1 more Smart Citation